The phthalocyanines applications in photodynamic therapy investigated by time-resolved and steady-state photothermal methods - Danuta Frackowiak; Krzysztof Wiktorowicz; Alfons Planner; Aneta Waszkowiak; Rodica-Mariana Ion (International Journal of Photoenergy)
The time-resolved photothermal methods are used in order to establish the yield of intersystem (singlet-triplet) crossing of dyes that are candidates for the application in photodynamic therapy. It is known that molecules with long living triplet state cause efficient photosensitization by direct interaction with the cells or by singlet oxygen generation.